Adverse prognosis associated with asymmetric myocardial thickening in aortic stenosis. (30th March 2017) - Kwiecinski, Jacek; Chin, Calvin W L; Everett, Russell J; White, Audrey C; Semple, Scott; Yeung, Emily; Jenkins, William J; Shah, Anoop S V; Koo, Maria; Mirsadraee, Saeed; Lang, Chim C; Mills, Nicholas; et al.
Abstract: Aims: Asymmetric wall thickening has been described in patients with aortic stenosis. However, it remains poorly characterized and its prognostic implications are unclear. We hypothesized this pattern of adaptation is associated with advanced remodelling, left ventricular decompenzation, and a poor prognosis. Methods and results: In a prospective observational cohort study, 166 patients with aortic stenosis (age 69, 69% males, mean aortic valve area 1.0 ± 0.4 cm 2 ) and 37 age and sex-matched healthy volunteers underwent phenotypic characterization with comprehensive clinical, imaging, and biomarker evaluation. Asymmetric wall thickening on both echocardiography and cardiovascular magnetic resonance was defined as regional wall thickening ≥ 13 mm and > 1.5-fold the thickness of the opposing myocardial segment. Although no control subject had asymmetric wall thickening, it was observed in 26% ( n = 43) of patients with aortic stenosis using magnetic resonance and 17% ( n = 29) using echocardiography. Despite similar demographics, co-morbidities, valve narrowing, myocardial hypertrophy, and fibrosis, patients with asymmetric wall thickening had increased cardiac troponin I and brain natriuretic peptide concentrations (both P < 0.001). Over 28 [22, 33] months of follow-up, asymmetric wall thickening was an independent predictor of aortic valve replacement (AVR) or death whether detected by magnetic resonance [hazard ratio (HR) = 2.15; 95% confidence interval (CI) 1.29–3.59; P = 0.003] or echocardiography (HR = 1.79; 95% CI 1.08–3.69; P = 0.021). Conclusion: Asymmetric wall thickening is common in aortic stenosis and is associated with increased myocardial injury, left ventricular decompenzation, and adverse events. Its presence may help identify patients likely to proceed quickly towards AVR. Clinical Trial Registration: https://clinicaltrials.gov/show/NCT01755936 : NCT01755936.